Analysis of the Implementation of Traffic Management at the Johor Roundabout Jalan Karya Wisata-Medan Johor - Bimantara, Dennis; Lubis, Marwan; Pasaribu, Bangun (CV. Rayyan Dwi Bharata, 2024)
Johor Roundabout is located on Jalan Karyawisata kec, Medan Johor, or more precisely right in front of the entrance to the J-City complex. This roundabout was just built in the 12th month of 2023. The existence of this roundabout has a detrimental impact on the speed of vehicles passing through the roundabout. The aim of this thesis is to analyze the performance of roundabouts using the MKJI1997 method. This survey was carried out by conducting research for 7 days, where each day I conducted a survey for 12 hours, namely from 07:00 to 19:00. After carrying out the survey, it was also found that the peak hour occurred on Monday at 17:00-18:00 where it was obtained that the total inflow was 7854 PCU/hour with the composition of Light Vehicles (LV) 3127 Pc/hour, Heavy Vehicles (HV) 322 PCU/hour and , motorbike (MC) 2189Smp/hour, and the results also obtained for the degree of saturation, namely 1.094, which means that the level of service for the roundabout is at F (i.e. traffic flow conditions are relatively low).